1999
DOI: 10.1055/s-2007-1013128
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine Inhibits Inducible NOS and Reverses Cardiac Dysfunction Late After Ischemia and Reperfusion - Implications for iNOS-Mediated Myocardial Stunning

Abstract: The present data indicate that induction of myocardial iNOS after 48 h I/R contributes to the development of reversible left-ventricular dysfunction, suggesting the involvement of iNOS in myocardial stunning. Whereas L-arginine is associated with further reduction of left-ventricular contractility, continuous inhibition of iNOS activation by AMG improves left-ventricular performance; this may be a novel and clinically important therapeutic modality in certain disease states associated with I/R, including cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Later studies (2,15,17,22,27,28) observed a gradual reappearance of protection within 24 h after the initial ischemic stimulus and with a longer duration of effect (3-4 days), which has been termed SWOP or the delayed phase of preconditioning. Several proteins have been identified as possible mediators of SWOP, including NOS, cyclooxygenase-2, ATP-sensitive K ϩ channels, antioxidant enzymes, and heat stress proteins (2,4,12,13,30). Considerable evidence (2,4,13,15,17,27,28,31) supports the concept that NO is a mediator of the SWOP in both coronary vessels and myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies (2,15,17,22,27,28) observed a gradual reappearance of protection within 24 h after the initial ischemic stimulus and with a longer duration of effect (3-4 days), which has been termed SWOP or the delayed phase of preconditioning. Several proteins have been identified as possible mediators of SWOP, including NOS, cyclooxygenase-2, ATP-sensitive K ϩ channels, antioxidant enzymes, and heat stress proteins (2,4,12,13,30). Considerable evidence (2,4,13,15,17,27,28,31) supports the concept that NO is a mediator of the SWOP in both coronary vessels and myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…MITU is a completely different chemical entity from AMG; however, both demonstrated similar effects in aged WT mice but did not affect aged iNOS-KO-mouse hemodynamic function. Using bolus administration in the infarct model, Wildhirt demonstrates a specific linear relationship between AMG accumulations in tissues where elevated iNOS activity existed (Wildhirt et al, 1999). Both i.v.…”
Section: Inos Inhibition or Catecholamine Effectsmentioning
confidence: 99%
“…In an experimental study, the authors reported that cardiac dysfunction development was accompanied by an increased myocardial iNOS activity. These authors suggested that aminoguanidine signifi cantly decreased iNOS activity and improved left ventricular performance in myocardial stunning (29). In our study, it was determined that AG and MP treatment signifi cantly decreased iNOS expression relative to CONT group.…”
Section: Discussionmentioning
confidence: 48%